Revealing the Karomah and Contributions of Kyai Basyirun: A Study of Oral Literature and Social Transformation in Malang - Nabila, Nadia; Kholiq, Kholiq (Edudeena : Journal of Islamic Religious Education, 2024)
This research is motivated by two things, namely the existence of oral literature studies which are starting to erode, especially in the Karangsuko Malang community and the existence of documentation of the life history of Kyai Basyirun, a cleric who had extraordinary karomah. This research aims to reveal the character that Kyai Basyirun has and his work towards the people of Karangsuko Malang. The research method uses descriptive qualitative with pragmatic research type. Data collection techniques use interviews and documentation. The data analysis technique uses inductive data analysis. The research results show that Kyai Basyirun has a Karomah that can be reached by the five human senses. All of this can be witnessed by those closest to him so that mystical things can be proven by existing witnesses. His contribution to society was enormous and was able to bring about significant change for the better. In reviewing Islamic Studies, Karomah Kyai Basyirun is able to cover six fields, namely the fields of Sufism, Islamic Theology, Social Religious Affairs, Islamic Epistemology, Fiqh, and Education and Culture. Abstrak: Penelitian ini dilatarbelakangi oleh dua hal, yakni keberadaan kajian sastra lisan yang mulai terkikis khususnya di masyarakat Karangsuko Malang dan keberadaan dokumentasi riwayat kehidupan Kyai Basyirun, seorang ulama yang memiliki karomah yang luar biasa. Penelitian ini bertujuan untuk mengungkap karomah yang dimiliki Kyai Basyirun dan kiprah beliau kepada masyarakat Karangsuko Malang. Metode penelitian menggunakan Kualitatif Deskriptif dengan jenis penelitian pragmatis. Teknik pengumpulan data menggunakan wawancara dan dokumentasi. Teknik analisis data menggunakan analisis data induktif. Hasil penelitian menyebutkan bahwa Kyai Basyirun memiliki Karomah yang dapat dijangkau oleh panca indra manusia. Kesemua ini bisa disaksikan oleh orang-orang terdekatnya sehingga hal-hal yang bersifat mistik mampu dibuktikan oleh saksi yang ada. Kiprah beliau pada masyarakat sangatlah besar dan mampu membawa perubahan kearah yang lebih baik secara signifikan. Dalam tinjauan Studi Islam, Karomah Kyai Basyirun mampu mencakup enam bidang, yakni bidang Tasawuf, Teologi Islam, Sosial Keagamaan, Epistemology Keislaman, Fiqih, serta Pendidikan dan Kebudayaan.